Staggered contracts and unemployment during recessions - Effrosyni Adamopoulou; Luis Díez-Catalán; Ernesto Villanueva (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
This paper studies the impact of downward wage rigidity on wage and employment dynamics after the outbreak of major recessions in Spain. Downward wage rigidity stems from collective agreements, which set province-sector-skill specific minimum wage floors for all workers. By exploiting variation in the renewal of collective contracts, we find that agreements signed before the onset of recessions settle on higher nominal negotiated wage growth than agreements signed after. Leveraging Social Security data and the distribution of the worker-level bite of minimum wage floors, we document that the negotiated wage rigidity translated into higher wage growth mainly among workers with wages close to the floors. Consequently, these workers experienced a substantial and highly persistent increase in the probability of non-employment but only if they were covered by collective agreements of long duration. Our findings highlight the interplay between rigidity at different parts of the wage distribution and labor market institutions and identify conditions under which collective contract staggering and the inability to renegotiate may amplify aggregate shocks.
Keywords: J23; J31; J50; 330; Employment; Job Separation; Collective Bargaining; Wage Rigidity; Staggering; Social Security Data